(untitled) (Research, Society and Development, 2021)
The objective of the present work was to characterize the arboreal vegetation of the riparian forest of Rio do Peixe, in the Natural Monument of Vale dos Dinossauros (MONA), in Sousa-PB. Trees were measured in 20 square sampling units of 400 m², arranged on the banks of the Rio do Peixe, in an equidistant manner. The circumference of the fuste at 1.30 m from the ground and at 0.3 m from the ground of the arboreal individuals with circumference at breast height (1.3 m) greater than or equal to 6 cm were measured with a measuring tape, in addition to the total height of the individuals, with the aid of graduated rod. Were evaluated floristic, diversity, evenness, and horizontal and vertical structures, in addition to diametric distribution. Were identified 919 individuals, 16 botanical families, 32 genera and 35 species. The most representative botanical families in number of individuals were the Fabaceae Linl. a Combretaceae R. Br., Fabaceae being the most representative in number of species. The area presents good floristic diversity and good distribution of individuals per species. The specie more importance and abundance in the area was Combretum leprosum Mart. (mofumbo) with 32% of the individuals sampled and 16.69% of the importance value. The species Cenostigma pyramidale (Tul.) Gagnon & G.P.Lewis., Senegalia bahiensis (Tul.) Gagnon & G.P.Lewis e Pseudobombax marginatum (A.St.-Hil., Juss. & Cambess.) A. Robyns were less abundant, with one individual each. Diametric distribution showed behavior characteristic of natural populations, in inverted-J. There is a strong presence of exotic species in the area, but in was found the sample, the presence of Prosopis juliflora (Sw) DC., Leucaena leucocephala (Lam.) de Wit., Cryptostegia madagascariensis Bojer. e Malpighia glabra L., species that naturally should not exist in the area.